2019
DOI: 10.1007/s11136-019-02393-5
|View full text |Cite
|
Sign up to set email alerts
|

Capability instruments in economic evaluations of health-related interventions: a comparative review of the literature

Abstract: Purpose Given increasing interest in using the capability approach for health economic evaluations and a growing literature, this paper aims to synthesise current information about the characteristics of capability instruments and their application in health economic evaluations. Methods A systematic literature review was conducted to assess studies that contained information on the development, psychometric properties and valuation of capability instruments, or their application in economic evaluations. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 110 publications
3
57
0
Order By: Relevance
“…Prerequisite for the latter should be the availability of potential instruments for income. On a different note, while there are first applications, more conceptual and theoretical work is needed about whether, when and how capability well-being should be included in health economic evaluations [58]. One open question for example is, whether full capability or a sufficient level of capability, which was established recently, should be considered as the objective of interventions [59].…”
Section: Interpretation and Implications Of The Resultsmentioning
confidence: 99%
“…Prerequisite for the latter should be the availability of potential instruments for income. On a different note, while there are first applications, more conceptual and theoretical work is needed about whether, when and how capability well-being should be included in health economic evaluations [58]. One open question for example is, whether full capability or a sufficient level of capability, which was established recently, should be considered as the objective of interventions [59].…”
Section: Interpretation and Implications Of The Resultsmentioning
confidence: 99%
“…For all indices, a value of < 0.2 was considered small, 0.2-0.5 moderate and > 0.5 large responsiveness [23]. The range of the un-weighted score was 16 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and for the tariff score was 1 (0-1) with higher scores on both representing higher capability. Age differences in responsiveness were investigated by subgroup analysis using a group < 65 years of age and a group ≥ 65 years of age.…”
Section: Responsivenessmentioning
confidence: 99%
“…A systematic review by Afentou and Kinghorn [9] and a comparative review by Helter et al [10] found evidence available on reliability, content validity, construct validity and responsiveness of the ICECAP-A measure in various populations, but so far, most evidence relates to the original UK version [9,10]. In the Danish context, only one reliability study of the ICECAP-A in the general population exists [11].…”
Section: Introductionmentioning
confidence: 99%
“…This approach places emphasis on promoting wellbeing through enabling people to realise their capabilities and engage in behaviours that they value (3). There is increasing interest in the use of the capability approach for the economic evaluation of health-related interventions (4). One reason for this is the wider evaluative space this approach offers in comparison to the commonly used methods of assessment (5).…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature review of capability instruments in economic evaluations of health-related interventions has identi ed 14 instruments, differing in their domains, levels, target populations and interventions (4). Two of these instruments are commonly used and have been validated for the adult population with mental health problems: the Oxford CAPabilities questionnaire-Mental Health (OxCAP-MH) and the ICECAP measure for Adults (ICECAP-A).…”
Section: Introductionmentioning
confidence: 99%